The Implication of Political Risk and Specific Macroeconomic Variables on Total Revenue in Tourism Industry - Habanabakize, Thomas; Mothibi, Lerato (International Journal of Economics and Financial Issues, 2024)
Political risk is one factor that influences tourism performance as a tourist is more sensitive to the hosting country’s political environment. In addition, to the effect of country risk on the tourism industry, the global economy has recently experienced severe shocks due to high inflation rates, political risk, and currency volatility. This paper aims to investigate the implications of political risk, inflation, and exchange rate volatilities on tourism revenue in South Africa. A sample of 144 monthly data was used to assess both long-run and short-run relationships amongst the study variables using the ARDL cointegration and error correction model approaches to achieve the study objective. Results indicated that political risk, inflation rate, and exchange rate volatility influence long-term revenue changes in the tourism industry. In contrast, real effective exchange rates and inflation significantly impact total revenue in the tourism sector. The findings also indicated that political risk has no short-term effect on tourism revenue. Based on these findings, the study recommends that the country's political stability increase, increasing the number of tourist arrivals and resulting in growing revenue for the tourism industry in S.A. Additionally, the South African reserve bank should revise its exchange-rate pegging, monetary targeting, and inflation targeting to reduce the effects of inflation on tourism revenue.